2021
DOI: 10.1007/s00383-020-04788-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of surgical timing of congenital diaphragmatic hernia using the quantified flow patterns of patent ductus arteriosus

Abstract: Purpose The optimal timing of surgery for congenital diaphragmatic hernia (CDH) is controversial. We aimed to validate our protocol for the timing of CDH repair using the quantified patent ductus arteriosus (PDA) flow pattern. Methods This retrospective comparative study analyzed patients with a prenatal diagnosis of isolated CDH between 2007 and 2020. We defined the "LR ratio" as the percentage of velocity-time integral (VTI) of the left-to-right flow of PDA against overall VTI on echocardiography. Since 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…However, these markers did not predict the occurrence of PH in a recent systematic review ( 18 ). In addition, PH has been discussed as an important guiding parameter in the timing of the surgical repair ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these markers did not predict the occurrence of PH in a recent systematic review ( 18 ). In addition, PH has been discussed as an important guiding parameter in the timing of the surgical repair ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…24 PDA blood ow patterns can act as reliable indicators of neonatal PH for optimal CDH repair timing, with the best intervention period being when PDA blood ow shifts to a left-to-right shunt. 25 This case re ects such an approach, determining surgery timing based on continuous echocardiographic monitoring of pulmonary artery pressure and PDA blood ow patterns under iNO or sildena l treatment. This case also illustrates that pre-ECMO cannulation surgery can promptly restore normal anatomy, alleviate thoracic compression, and create space for lung expansion.…”
Section: Case Presentationmentioning
confidence: 98%
“…Advances in medical therapies during the past decade(s) have steadily improved CDH mortality. However, high mortality rates are observed during the rst days to weeks of life due to aggravation of CDH-PH following birth [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A study from the UK in 2012 showed the best OI on day 1 of life as a strong predictor of survival in CDH [9]. Because PH is altered by (i) various kinds of stressors (ii) pulmonary compliance mechanics (iii) active ventilator management and (iv) cardiopulmonary stabilisation strategy -a single best OI may not be representative of overall lung function [4,7,10]. Tan et al [7] proposed that a serial OI measured during the rst 24hours of life may potentially better guide early CDH management as well as setting realistic expectations of a newborns subsequent response to intensive care therapy(s).…”
Section: Introductionmentioning
confidence: 99%